Using observable trade data to measure bilateral trade costs in sub-Saharan Africa - Festus Ebo Turkson (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2012)
Following closely the analytical approach adopted by Head and Mayer (2004) and Novy (2010), this paper derives a micro-founded bilateral trade cost measure for sub-Saharan Africa (SSA) as a function of observable domestic and inter-national trade data. The derived measure of trade cost by Novy (2010), consistent with the Ricardian and heterogeneous firm's models of trade, enables us to track changes in trade costs in SSA over time. This is a significant contribution to the trade cost literature in SSA because measures of many components of trade frictions in SSA have been unreliable. Based on bilateral trade data from BACI and production figures from the Trade, Production and Protection database by Nicita and Olarreaga (2007) for the period 1980-2003, our estimates of the tariff equivalent bilateral trade costs measure indicate that on average trade costs in SSA are relatively higher than other regions, confirming evidence which indicates trading costs in SSA to be the highest within the global trading system. The estimates indicate that SSA countries traded with each other at a lower cost than they did with other regions with the exception of the EU. Within SSA, member countries of economic blocs traded at relatively lower costs than trade with non-member countries. Using each of the main five economic blocs within SSA as a reference, overall average relative bilateral trade costs within bloc was significantly lower than across blocs. This paper therefore argues for increased efforts at regional integration within SSA to derive benefits from lower trade costs.
Keywords: F10; F13; F14; O55; O57; 330; Trade Costs; Gravity Model; Bilateral Exports; Sub-Saharan Africa